HEALTH COUNSELING PROGRAM: SCABIES-FREE INTELLECTED COMMUNITIES - Marsela Riska Raswandaru; Rosiana Eva Rayanti; Presty Adventri; Ren Sisca Novia; Juli Marjaya Zai; Threceya Rambu Lika Handja Analalo; Rachel Theananda Sari (Magistrorum et Scholarium: Jurnal Pengabdian Masyarakat, 2023)
Scabies is an infectious disease caused by the mite Sarcoptes scabei var hominis. This disease develops in communities with dense, damp housing and poor environmental sanitation. The purpose of community service is to provide health education about scabies and increase the knowledge of prisoners about scabies disease and wound care. Community service is carried out by providing health education and demonstrations of wound care. The result of community service is that the knowledge of the inmates regarding scabies can increase and the inmates can take care of scabies wounds independently. Community service participants can participate in activities actively and enthusiastically. Evaluation of community service is carried out by giving questions orally, filling out pre-post test questions, and filling out activity evaluation sheets. The scabies-free outreach program for prisoners is important to carry out routinely because it has positive impacts such as increasing personal hygiene and increasing the knowledge of prisoners.